Image Based Steganography to Facilitate Improving Counting-Based Secret Sharing - Gutub, Adnan; Al-Ghamdi, Maimoona (3D research, 2019)
The secret sharing scheme is a security tool that provides reliability and robustness for multi-user authentication systems. This work focuses on improving the security and efficiency of counting-based secret sharing by remodeling its phases. The research presents refining the shares generation phase as well as proposing different secret reconstruction models based on new shares distribution method. This work addressed solving published defects in the original counting-based secret sharing scheme providing optimized efficient methodology. The research further proposed utilizing steganography for practicality purposes. We adopted image-based steganography to hide generated shares preserving the improved security of the scheme enhancing the humanized remembrance usability. The study compared several applicable steganography methods for hiding shares analyzing their distortion, security, and capacity. This facilitating work of image-based steganography with the improved counting-based secret sharing is showing promising results opening research direction for future attractive contributions to follow-on.